ANALISIS FUNGSI PRODUKSI DAN SPASIAL PRODUKTIVITAS NANAS DI KECAMATAN TAMBANG KABUPATEN KAMPAR - Afifah Nurul Humairah; Yudi Antomi (DEPARTEMEN GEOGRAFI FIS UNP, 2022)
The purpose of this research are (1) to find the productivity of pineapple in each pineapple farms and hamlet, (2) factors that affect the pineapple productivity, (3) elasticity of pineapple productivity, and (4) the interrelation of factors that significantly influence the pineapple productivity in Tambang District, Kampar Regency. The type of research is a verifiable descriptive with a quantitative approach. The data used in this study are the pineapple productivity data, production of pineapple, land area, labor, seed, fertilizer, and pineapple farms shapefile. The analysis used are Cobb-Douglas production function and generalized linear regression. The results show that pineapple productivity in the Tambang district has an average of 41 ton/ha and the highest productivity is in the sub-village 1, Kualu Nenas Village. The factors affecting the pineapple productivity in the Tambang are land area, labor, the type of seed, and fertilizer that used. The whole factor of production is inelastic. The high pineapple productivity has a small area of land, a high work force, uses stem-bud seeds, and a lot of fertilizer and corresponds to what agriculturan r&d defines with a very low-low interpretation.